PENERAPAN MODEL QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD NEGERI 188 PEKANBARU - Ade Lis Pratiwi; Syahrilfuddin '; Mahmud Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is based on the fact that found in the fourth year students of SD Negeri 188 Pekanbaru, that is the students’ achievement in learning mathematics is still low . From 32 students, there were only 18 students (56,25%) whose scores above the KKM with an average of 67,71. Based on that fact, the implementation of a learning model is able to help students to improve their achievement, the model is Quantum Teaching model. The Quantum Teaching Model is a vibrant learning alteration with all its nuances that include all the connections, interactions and differences that maximize the moments of learning and focus on dynamic relationships within the classroom environment. The objective of this research is to improve the students’ achievement on mathematics learning by applying the model of Quantum Teaching on the fourth year students of SD Negeri 188 Pekanbaru. This research was conducted for 2 cycles. The data collections in this research are the teachers and students’ activity and also the students’ results on their daily test in every cycle. The teachers’ activity increased by 70,8% (enough) and 79,2% (good) in cycle I and 87,5% (very good) and 95,8% (very good) in cycle II. It also occurred in student’ activity with 66,7% (enough) and 75% (enough) in cycle I and 87,5% (very good) and 95,8% (very good) in cycle II. In addition to teachers’ and students’ activity, students' achievement on mathematics learning also increased from the average base score of 67,71 with a completeness percentage of 56,25% increased in the first cycle by 4,66 points (6,88%) to 72,37 with Percentage 78,12%. In the second cycle again increased from 72,37 to 82,75 with an increase of 10,38 points (22,2%) with the percentage of students’ mastery of 87,50%. So from the data that is obtained, the conclusion in this research is the Quantum Teaching model improved the students' mathematics achievement on the fourth year students of SD Negeri 188 Pekanbaru.Keywords: Quantum Teaching Model, Mathematics learning achievement.